Khazanah Tradisi Astronomi dan Astrologi Masyarakat Sulawesi Selatan - Fatmawati Fatmawati; Andi Muhammad Akmal; Fathur Rahman Basir (University of Muhammadiyah Sumatera Utara, 2022)
Ethnoastronomy is one of the oldest studies that is closely related to myths, way of life, heritage objects in the form of temples/statues, and traditional/religious ceremonies of a community that has its own style and values. This then gave birth to a variety of traditions including ethnoastronomy which are connected with Astronomy which are interpreted by the people of South Sulawesi in various aspects, such as religion, socio-culture, science, and community dynamics. The method used in this study is descriptive qualitative using socio-historical, ethnological, and iconographic approaches. Data collection was obtained from a textual study. The results of this study conclude that ethnoastronomy and astrology are mutually affiliated with Astrology. However, what distinguishes it is that the source of Astrology does not conflict with the Qur'an and hadith, also that astronomy includes hablum minallah, hablum minannas, and hablum minal alam, namely the relationship between Allah, humans, and nature.